Prospective non-randomized study of preoperative concurrent platinum plus 5-fluorouracil-based chemoradiotherapy with or without paclitaxel in esophageal cancer patients: long-term follow-up - Zemanova, M; Petruzelka, L; Pazdro, A; Kralova, D; Smejkal, M; Pazdrova, G; Honova, H (Diseases of the esophagus, 2010)
Combined modality treatment for esophageal carcinoma seems to improve survival over surgery alone. Different combinations of cytotoxic drugs have been studied to improve antitumor efficacy and limit the toxicity of chemoradiotherapy (CRT) with inconsistent results. We present a prospective study of neoadjuvant CRT with or without paclitaxel in chemotherapy schedule. One hundred seven patients (93 males, 14 females), median age 59 years (range 44-76), with operable esophageal cancer were enrolled. They received the following neoadjuvant therapy: Carboplatin, area under curve (AUC) = 6, intravenously on days 1 and 22, 5-fluorouracil (5-FU), 200 mg/m(2)/day, continuous infusion on days 1 to 42, radiation therapy 45 grays/25fractions/5 weeks beginning on day 1. Forty-four patients (41%) were furthermore non-randomly assigned to paclitaxel 200 mg/m(2)/3 h intravenously on days 1 and 22. Nutritional support from the beginning of the treatment was offered to all patients. Surgery was done within 4-8 weeks after completion of CRT, if feasible. All patients were evaluated for grade 3 plus 4 toxicities: leukopenia (28%), neutropenia (30%), anemia (6%), thrombocytopenia (31%), febrile neutropenia (6%), esophagitis (24%), nausea and vomiting (7%), pneumotoxicity (8%). Seventy-eight patients (73%) had surgery and 63 of them were completely resected. Twenty-two patients (20%) achieved pathological complete remission, and additional 20 (19%) had node-negative and esophageal wall-positive residual disease. There were 10 surgery-related deaths, mostly due to pulmonary insufficiency. Twenty-nine patients were not resected, 15 for early progression, 14 for medical reasons or patient refusal. After a median follow-up of 52 months (range 27-80), median survival of 18.0 months and 1-, 2-, 3- and 5-year survival of 56.7, 37.5, 27.0 and 21% was observed in the whole group of 107 patients. Addition of paclitaxel to carboplatin and continual infusion of FU significantly increased hematologic and non-hematologic toxicity, but treatment results as overall survival or time to progression did not differ significantly in groups with and without paclitaxel. Patients achieving pathological complete remission or nodes negativity after neoadjuvant therapy had favorable survival prognosis, whereas long-term prognosis of node positive patients was poor. Distant metastases prevailed as a cause of the treatment failure. Factors significant for survival prognosis in multivariate analysis were postoperative node negativity, performance status, and grade of dysphagia. Addition of paclitaxel to carboplatin and continual FU significantly increased hematologic and non-hematologic toxicity without influencing efficacy of the treatment. This study confirmed improved prognosis of patients after achieving negativity of nodes. Distant metastases prevailed as cause of the treatment failure. Prospectively, it is important to look for a therapeutic combination with better systemic effect.
Keywords: Aged; výsledek terapie; Antimetabolites, Antineoplastic; indukce remise; Survival Rate; Antineoplastic Combined Chemotherapy Protocols; Neutropenia; nádory jícnu; Longitudinal Studies; Paclitaxel; leukopenie; fluoruracil; protokoly protinádorové kombinované chemoterapie; lidé; ženské pohlaví; senioři; lidé středního věku; Radiotherapy, Adjuvant; Fluorouracil; Chemotherapy, Adjuvant; protinádorové antimetabolity; ezofagitida; Dose Fractionation, Radiation; Esophagitis; Carcinoma, Squamous Cell; mužské pohlaví; Female; adjuvantní radioterapie; frakcionace dávky záření; Remission Induction; Adult; Follow-Up Studies; neutropenie; Middle Aged; Antineoplastic Agents, Phytogenic; trombocytopenie; neoadjuvantní terapie; spinocelulární karcinom; Antineoplastic Agents; Treatment Outcome; Leukopenia; míra přežití; Humans; Thrombocytopenia; karboplatina; protinádorové látky; prospektivní studie; dospělí; Male; Esophageal Neoplasms; následné studie; longitudinální studie; Carboplatin; paclitaxel; Neoadjuvant Therapy; Prospective Studies; adjuvantní chemoterapie; fytogenní protinádorové látky